Magnesium Stable Isotope Fractionation on a Cellular Level Explored by Cyanobacteria and Black Fungi with Implications for Higher Plants - Pokharel, Rasesh; Gerrits, Ruben; Schuessler, Jan A; Frings, Patrick J; Sobotka, Roman; Gorbushina, Anna A; von Blanckenburg, Friedhelm (Environmental science & technology, 2018)
In a controlled growth experiment we found that the cyanobacterium Nostoc punctiforme has a bulk cell 26Mg/24Mg ratio (expressed as δ26Mg) that is -0.27‰ lower than the growth solution at a pH of ca. 5.9. This contrasts with a recently published δ26Mg value that was 0.65‰ higher than growth solution for the black fungus Knufia petricola at similar laboratory conditions, interpreted to reflect loss of 24Mg during cell growth. By a mass balance model constrained by δ26Mg in chlorophyll extract we inferred the δ26 Mg value of the main Mg compartments in a cyanobacteria cell: free cytosolic Mg (-2.64‰), chlorophyll (1.85‰), and the nonchlorophyll-bonded Mg compartments like ATP and ribosomes (-0.64‰). The lower δ26Mg found in Nostoc punctiforme would thus result from the absence of significant Mg efflux during cell growth in combination with either (a) discrimination against 26Mg during uptake by desolvation of Mg or transport across protein channels or (b) discrimination against 24Mg in the membrane transporter during efflux. The model predicts the preferential incorporation of 26Mg in cells and plant organs low in Mg and the absence of isotope fractionation in those high in Mg, corroborated by a compilation of Mg isotope ratios from fungi, bacteria, and higher plants.
Keywords: Magnesium; chemická frakcionace; Chemical Fractionation; rostliny; Nostoc; hořčík; izotopy; Isotopes; Plants